Breaking It Down: Investigation of Binge Eating Components in Animal Models to Enhance Translation - Hildebrandt, Britny A.; Ahmari, Susanne E. (Frontiers in Psychiatry, 2021)
Binge eating (BE) is a core eating disorder behavior that is present across nearly all eating disorder diagnoses (e.g., bulimia nervosa, binge eating disorder, anorexia nervosa binge/purge subtype), and is also widely present in the general population. Despite the prevalence of BE, limited treatment options exist and there are often high rates of relapse after treatment. There is evidence showing that genetic factors contribute to the heritability of BE and support for biological contributions to BE. However, more work is needed to fully understand neurobiological mechanisms underlying BE. One approach to target this problem is to separate BE into its distinct clinical components that can be more easily modeled using pre-clinical approaches. To date, a variety of animal models for BE have been used in pre-clinical studies; but there have been challenges translating this work to human BE. Here, we review these pre-clinical approaches by breaking them down into three clinically-significant component parts–1) consumption of a large amount of food; 2) food consumption within a short period of time; and 3) loss of control over eating. We propose that this rubric identifies the most frequently used and effective ways to model components of BE behavior using pre-clinical approaches with the strongest clinical relevance. Finally, we discuss how current pre-clinical models have been integrated with techniques using targeted neurobiological approaches and propose ways to improve translation of pre-clinical work to human investigations of BE that could enhance our understanding of BE behavior.